2019
DOI: 10.1021/acsami.8b21197
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-Inspired Self-Healing Coatings Based on Polydopamine-Coated Nanocontainers for Corrosion Protection

Abstract: The mussel-inspired properties of dopamine have attracted immense scientific interest for surface modification of nanoparticles due to the high potential of dopamine functional groups to increase the adhesion of nanoparticles to flat surfaces. Here, we report for the first time a novel type of inhibitor-loaded nanocontainer using polydopamine (PDA) as a pH-sensitive gatekeeper for mesoporous silica nanoparticles (MSNs). The encapsulated inhibitor (benzotriazole) was loaded into MSNs at neutral pH, demonstratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 179 publications
(52 citation statements)
references
References 46 publications
3
49
0
Order By: Relevance
“…The released healing chemistry then repairs the damage. In coatings, self‐healing has been achieved with micro‐ and nanocapsules containing core materials such as linseed oil, polydimethylsiloxanes (PDMSs), polyurethanes (PUs), or silyl esters . Scribe damage to the coating exposes the substrate, ruptures the capsules, and releases the healing material.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The released healing chemistry then repairs the damage. In coatings, self‐healing has been achieved with micro‐ and nanocapsules containing core materials such as linseed oil, polydimethylsiloxanes (PDMSs), polyurethanes (PUs), or silyl esters . Scribe damage to the coating exposes the substrate, ruptures the capsules, and releases the healing material.…”
Section: Introductionmentioning
confidence: 99%
“…Behzadnasab et al showed that larger capsules can lead to better healing performance through visual inspection of the coatings. Qian et al used a bioinspired healing system to prevent corrosion and provide the sustained release of the healing agent . Cho et al incorporated a two‐part (poly)dimethyl siloxane (PDMS)‐based healing chemistry in polymer microcapsules .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the coincide of the characteristic peaks of PAN and epoxy resin, and the few amounts of epoxy and triethylenetetramine, the characteristic peaks of the two healing agents in the core-shell fibers IR was not obvious. PAN, as a good container [ 50 , 51 , 52 ] in encapsulating the two reactive healing agents, will be further judged by thermal stability.…”
Section: Resultsmentioning
confidence: 99%